ANALISIS ASPEK KEPRIBADIAN TOKOH UTAMA DIVA DALAM NOVEL “MUHASABAH CINTA” KARYA DINI FITRIA - Ali Manshur; Muhammad Arif Rahman Hakim (Jurnal Tarbiyatuna: Jurnal Kajian Pendidikan, Pemikiran dan Pengembangan Pendidikan Islam, 2020)
Personality is the life of a person as a whole, individually, unique, effort to achieve goals, ability to survive and open up, ability to gain experience. This personality is influenced by the use of the three personality systems in Sigmund Freud's theory, namely the id, ego, and superego. There are three research problem formulations, namely (1) How is the personality aspect related to the main character Diva's id in the novel "Muhasabah Cinta" by Dini Fitria, (2) How is the personality aspect related to Diva's main character's ego in the novel "Muhasabah Cinta" by Dini Fitria, (3) How is the personality aspect related to the main character superego Diva in the novel "Muhasabah Cinta" by Dini Fitria. The purpose of this study are (1) Describe the personality aspects related to the main character id Diva in the novel "Muhasabah Cinta" by Dini Fitria, (2) Describe the aspects of personality related to the main character Diva in the novel "Muhasabah Cinta" by Dini Fitria , (3) Describe the personality aspects related to the main character superego Diva in the novel "Muhasabah Cinta" by Dini Fitria. This research uses descriptive qualitative method using Sigmund Freud's personality psychology approach. The object of this research is the psychological aspect which is focused on the personality of the main character of Diva according to Sigmund Freud's personality theory. The data source used in this study is the novel: "Muhasabah Cinta". Data collection techniques in this study are note-taking techniques. The data that has been collected is then processed and analyzed through several stages, namely the heuristic reading stage by interpreting the text and the hermeneutic reading stage by interpreting the meaning.